Environmental landscape and subsistence strategy of the Shunshanji Culture: A review - Qiu, Zhenwei; Rao, Huiyun (Frontiers in Plant Science, 2022)
The Shunshanji Culture is the earliest known Neolithic culture in the mid-lower Huai River. In recent years, with new discoveries and deeper studies of the Shunshanji Culture, the concept of the Shunshanji cultural site group has gradually formed. Among them, various types of rice remains have been unearthed in large quantities, which provide key materials for discussing rice farming, rice cultivation and domestication, and related issues in the Huai River Basin. Previous studies have conducted reconstruction of local vegetation landscape and analysis of subsistence strategies on some systematically excavated Shunshanji cultural sites and obtained some new understandings. Integrative research, however, is lacking. In this review, we combine the construction of the local environmental landscape with the settlement landform within the Shunshanji cultural site group and then incorporate it into the regional environmental evolution of the mid-lower Huai River. The consistency and difference in their subsistence were also summarized. In particular, we focus on the relevant clues of the early paddy field cultivation system in the region and perform comparative studies.